Engineering and Clinical Study of Surface Geometry of Clear Aligners at the Nanoscale - Machoy, Monika; Samulak, Renata; Kulesza, Sławomir (Applied sciences, 2024)
This paper investigates the evolution of the outer surface geometry of Invisalign®—clear orthodontic aligners—caused by degradation triggered by wearing. The obtained results served to confirm whether or not the aligners could continue to be used once their wear time in the therapeutic procedure had ended, taking both their geometric and mechanical features into account. The measurements were performed using atomic force microscopy which allowed the mapping of nanomechanical properties. The obtained images were then processed to determine statistical and functional surface geometry parameters in accordance with relevant ISO standards. The results revealed that the unrepeatability of the manufacturing process causes the surface shape parameters of new aligners to be irregular; however, these features become gradually consistent for worn samples. On the other hand, properly used aligners may change in two ways: the outer layer flattens and its thickness decreases, and at the same time the Young’s modulus of the material decreases. It follows that the degradation processes may be caused by tribological phenomena (abrasion of contact surfaces) and/or biochemical phenomena (biofilm growth, decomposition of the material under the influence of enzymes in the oral cavity).